A stretchable, environmentally tolerant, and photoactive liquid metal/MXene hydrogel for high performance temperature monitoring, human motion detection and self-powered application - Zhang, Wei; Wang, Pei-Lin; Huang, Ling-Zhi; Guo, Wen-Yan; Zhao, Jinjin; Ma, Ming-Guo (Nano energy, 2023)
Conductive gels have received extensive attention in flexible electronics due to their diverse characteristics. The requirement for versatility and incompatibility of the conductive fillers with the hydrogel matrix remain a challenge for hydrogels. Herein, the cellulose nanofiber stabilized liquid metal droplets are utilized to initiate the polymerization and simultaneously serve as solid conductive fillers to construct the polyacrylamide/MXene/glycerol hydrogel with eligible stretchability (1000%) and high environmental adaptability (−25 to 80 °C) for multifunctional sensing. The hydrogel is utilized as a flexible electrode to construct the triboelectric nanogenerator for mechanical energy harvesting and conversion as well as self-powered sensing. Importantly, as a versatile sensor, it combines temperature sensing and deformation sensing with a wide range of stimulus responses and exceptional sensing performance. The flexible temperature and strain sensors are realized with superior thermosensitivity and strain sensitivity. In addition, the hydrogel exhibits favorable photothermal antibacterial ability. This work opens new avenues for the preparation of photothermal, conductive, stress and thermal sensitive hydrogels for multimodal sensors, sketching a promising future for them in flexible and wearable electronics. [Display omitted] •CNF stabilized liquid metal droplets initiate the gelation process within two minutes.•Ti3C2Tx MXene nanosheets were introduced to establish more efficient conductive pathways.•Glycerol-water binary solvent enhanced adaptability of hydrogels in extreme environments.•The hydrogel achieves self-power and provide continuous human motion and temperature detection.•The hydrogel present remarkable photothermal synergistic antibacterial capabilities.